DFT calculations of Cu doped TiO2 ferromagnetic study - Wu Biao; Wu Jiang (E3S Web of Conferences, 2023)
There is still some controversy about the room-temperature ferromagnetism generated by transition metal-doped TiO2 and its magnetic generation. In this paper, the samples with different doping ratio were prepared to verify the magnetism of doped TiO2, and then the geometry of copper-doped Ti16O32 supercell system was optimized by using the overall energy density function theory (DFT) and generalized gradient approximation (GGA). The results show that the doped energy band diagram shows electron self-selective cleavage near the Fermi energy level and the addition of Cu atoms does produce ferromagnetism. The magnitude of the induced magnetic moment is related to the distance of Cu atoms and oxygen vacancies. The system with a doped Cu-Cu distance of 3.82 A is more stable, and the ferromagnetism of the doped phase is more stable and lower 29 meV than the antiferromagnetic state in the absence of oxygen vacancies (Cu2Ti14O32), while a magnetic burst occurs in Cu2Ti14O30 after the formation of oxygen vacancies. Magnetic Cu-TiO2 may become a promising adsorbent to be applied in the field of pollutant control.